Model Edukasi Akses KIP Kuliah dan Strategi Pengelolaan Keuangan Berbasis Experiential Learning bagi Siswa SMA/SMK dan Guru BK di Bandung Raya - Horas Djulius; Restu Akbar Suryaman; Gugum Mukdas Sudarjah; M. Sidik Priadana; Neni Murniati (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2026)
Purpose – This community service activity aims to address the procedural information gap regarding the Kartu Indonesia Pintar (KIP) Kuliah program and enhance fund management skills for Grade XII high school/vocational students and Guidance Counselors (BK Teachers) in the Bandung Raya region. The intervention is designed to ensure students have both access to higher education opportunities and essential fund management competencies Design/methodology/approach – The program was implemented using an experiential learning-based workshop model integrating offline and online sessions (blended approach), which involved practical simulation of the KIP Kuliah system application. Effectiveness was measured quantitatively through pre-tests and post-tests across two dimensions: KIP Kuliah Access and Financial Management Findings – Evaluation results showed a significant increase in understanding. KIP Kuliah Access Understanding increased by 43.1% (mean score from 2.51 to 4.02), and Financial Management Understanding increased by 38.8% (mean score from 2.38 to 3.86). This increase validates the program's success in bridging the information gap and providing applied solutions for the partners Originality/value – The program offers an original contribution by providing an integrated intervention that combines procedural problem solutions (KIP Kuliah Access) and managerial solutions (Financial Literacy) within a single experiential framework. Furthermore, the activity successfully strengthened the capacity building of Guidance Counselors, positioning them as sustainable change agents at the school level to better support students' study continuity